DOT-ELISA for detection of anti-Cysticercus cellulosae antibodies in human cerebrospinal fluid using a new solid-phase (resin-treated polyester fabrics): preliminary report - Vaz, Adelaide José; Ferreira, Antonio Walter; Camargo, Mário E.; Nakamura, Paulo Mutuko; Camargo, Eide Dias (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
A dot enzyme-linked immunosorbent assay (DOT-ELISA) was developed to detect specific antibodies in cerebrospinal fluid (CSF) for human neurocysticercosis immunodiagnosis, with Cysticercus cellulosae antigen dotted on a new solid-phase. This was represented by sheets of a synthetic polyester fabric impregnated with a polymerized resin (N-methylol-acrylamide). A very stable preparation was thus obtained, the antigen being covalently bound by cross-linking with free N-methylol groups on the resin. Since robust, no special care was necessary for handling the solid-phase. The test could be performed at room-temperature. From 30 CSF samples assayed, 14 were positive, from a group of 15 cases of neurocysticercosis, with titers from 1 to 128; 15 other samples, from normals or other neurological diseases, were all negative. Test characteristics seem to indicate it as adequate for epidemiological surveys. A more detailed study on sensitivity, specificity, reproducibility and the use in serum samples is being conducted.